Working with Black vs. White patients: an experimental test of therapist decision-making in cognitive behavioral therapy for depression. Issue 3 (4th May 2022) - Ezawa, Iony D.; Strunk, Daniel R.
ABSTRACT: Whether and how therapists' delivery of cognitive behavioral therapy (CBT) for depression differs by patients' ethnicity or race remains unclear. In this study, 218 therapists were randomized to clinical vignettes that involved the same text but varied in whether the accompanying image depicted a Black or White patient. Therapists exhibited three key differences in their views of clinical strategies for working with Black as compared to White patients. They viewed cognitive change strategies as less therapeutic and validation strategies as more therapeutic for Black patients. They reported similar differences for the time they would spend on each kind of strategy. When asked to compare the relative importance of cognitive change vs. validation strategies specifically, therapists rated validation as more important for Black than White patients. Among therapists presented with Black patients, positive racial attitudes were associated with viewing cognitive change and validation strategies as more therapeutic. These results suggest therapists tend to believe it is desirable to incorporate cognitive methods more limitedly when working with Black patients. Whether such adaptations enhance or detract from the care of Black patients is an important issue that merits future investigation.